Evaluation of SrAl2O4:Eu, Dy phosphor for potential applications in thermoluminescent dosimetry. Issue 5 (5th May 2021) - Tang, Xueyan; Ehler, Eric D.; Brost, Eric; Mathew, Damien C.
Abstract: Purpose: To evaluate the use of commercial‐grade strontium aluminate phosphorescent powder as a thermoluminescent (TL) dosimeter for clinical radiotherapy beams. Materials and Method: Commercially available Eu 2+, Dy 3+ co‐doped strontium aluminate powder (SrAl2 O4 :Eu, Dy) was annealed and then irradiated using 20 × 20 cm 2 field size, with 6‐MV (PDD10  = 70.7) and 18‐MV (PDD10  = 79.4) photon beams and and 9‐MeV (R50  = 3.6), 15 MeV (R50  = 5.9) and 18‐MeV (R50  = 7.2) electron beams. To calibrate the relationship between the TL readings and the irradiated doses, TL glow curves were acquired for doses up to 600 cGy at all beam energies. For the percentage depth dose (PDD) measurement, the SrAl2 O4 :Eu, Dy powder was sandwiched by solid water phantoms, with varying thickness of solid water placed above to determine the depth. PDDs were measured at four representative depths and compared against the commissioning depth dose data for each beam energy. Results: Linear dose response models of doses up to 200 cGy were created for all beam energies. Superlinearity was observed with doses greater than 200 cGy. The PDD measurement acquired experimentally agrees well with the commissioning data of the medical linear accelerator. Trapping parameters such as order of kinetics, activation energy and frequency factor have been obtained via TL glow curve analysis. Conclusion: The linear dose response demonstrates that SrAl2 O4 :Eu, Dy is a potential TLD dosimeter for both electron beams and photon beams at different beam energies. The PDD measurements further support its potential use in quality assurance and radiation dosimetry.